• FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGISIAN BUKU KIA OLEH BIDAN DALAM DETEKSI DINI RISIKO TINGGI KEHAMILAN DI PUSKESMAS KABUPATEN BANYUMAS TAHUN 2012 - Anasari, Tri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2013)
KIA book is one of early detection tools for high risk pregnancy. Utilization of KIA book by midwives in Banyumas district was not maximal. This was indicated by the high risk pregnancy early detection coverage that was still below the target (20%). In addition, the number of maternal death cases increased from 123.9/100.000 live birth in 2010 to 129.35/100.000 live births in 2011. The objective of this study was to know the influence of knowledge, supervision perception, motivation, facility support and workload towards the completeness of KIA book filling by midwives in early detection of high risk pregnancy in the primary healthcare centers (puskesmas) of Banyumas district. This was an observasional analytical study with cross sectional approach. Structured questionnaire was used as a research instrument. Data were collected through interview and observation. Study population was 495 midwives. Proportional random sampling was applied to obtain 84 samples. Bivariate analysis using chi-square test and multivariate analysis using logistic regression were apllied in the data analysis. Results of the study showed that most of the KIA books (60.7%) were completely filled; 82.1 % of respondents had good knowledge; and 51.2% of respondents had good perception on supervision. Proportion of respondents with low motivation was 51.2%, proportion of respondents with complete facility support was 53.6%; and proportion of respondents with heavy workload was 50%. Result of bivariate analysis showed that knowledge (p= 0.001), motivation (0.001), workload (p= 0.023) had positive associations with the completeness of KIA book filling. Multivariate analysis indicated the influence of knowledge (p=0.002; Exp B= 10.981), motivation (p=0.001; Exp B= 7.713) and workload (p=0.021; Exp B= 0,260) toward the completeness of KIA book filling. Recommendation addressed to Puskesmas is to form puskesmas task force team for the implemented programs; and it is intended to reduce midwives workload. Sugesstion for the head of Banyumas district health office is to provide rewards for midwives who have good achievement. Keywords: Completeness of KIA book filling, early detection of a high risk pregnancy